Perawatan Preventive Maintenance Mobil Satlantas Model Sedan Mazda dengan Metode Reliability Centered Maintenance pada Polres Kota X - Akbar, M. Rivaldi; Iskandar, Hendi; Ulum, Rikzan Bachrul (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to find out the preventive maintenance of Mazda Sedan Model Traffic Cars using the reliability centered maintenance method at the City functional block diagram, determining system function and functional failure, failure mode and effect analysis, logic tree analysis, and task selection. The results of this research are that the maintenance system for traffic vehicle units carries out routine check-ups every 5,000 kilometers or every 3 months and for brake and tire components every 10,000 kilometers or 6 months, the damage that appears with the current maintenance system is the break caliper (right front), hose (water pump), and ball joint, factors that arise with current maintenance problems are safety problems, proposed improvements that need to be made to resolve the problem are preventive maintenance for the break caliper (right front), hose (water pump), and ball joint every 11000 hours or 458 days.